Statins in Asthma: Potential Beneficial Effects and Limitations - Bhattacharjee, Dipanjan; Chogtu, Bharti; Magazine, Rahul (Pulmonary Medicine, 2015)
Asthma’s sustenance as a global pandemic, across centuries, can be attributed to the lack of an understanding of its workings and the inability of the existing treatment modalities to provide a long lasting cure without major adverse effects. The discovery of statins boosted by a better comprehension of the pathophysiology of asthma in the past few decades has opened up a potentially alternative line of treatment that promises to be a big boon for the asthmatics globally. However, the initial excellent results from the preclinical and animal studies have not borne the results in clinical trials that the scientific world was hoping for. In light of this, this review analyzes the ways by which statins could benefit in asthma via their pleiotropic anti-inflammatory properties and explain some of the queries raised in the previous studies and provide recommendations for future studies in this field.